Embedded star clusters and the formation of the Oort Cloud - Brasser, R.; Duncan, M.J.; Levison, H.F. (Icarus (New York, N.Y. 1962), 2006)
Observations suggest most stars originate in clusters embedded in giant molecular clouds [Lada, C.J., Lada, E.A., 2003. Annu. Rev. Astron. Astrophys. 41, 57–115]. Our Solar System likely spent 1–5 Myrs in such regions just after it formed. Thus the Oort Cloud (OC) possibly retains evidence of the Sun's early dynamical history and of the stellar and tidal influence of the cluster. Indeed, the newly found objects (90377) Sedna and 2000 CR 105 may have been put on their present orbits by such processes [Morbidelli, A., Levison, H.F., 2004. Astron. J. 128, 2564–2576]. Results are presented here of numerical simulations of the orbital evolution of comets subject to the influence of the Sun, Jupiter and Saturn (with their current masses on orbits appropriate to the period before the Late Heavy Bombardment (LHB) [Tsiganis, K., Gomes, R., Morbidelli, A., Levison, H.F., 2005. Nature 435, 459–461]), passing stars and tidal force associated with the gas and stars of an embedded star cluster. The cluster was taken to be a Plummer model with 200–400 stars, with a range of initial central densities. The Sun's orbit was integrated in the cluster potential together with Jupiter and Saturn and the test particles. Stellar encounters were incorporated by directly integrating the effects of stars passing within a sphere centred on the Sun of radius equal to the Plummer radius for low-density clusters and half a Plummer radius for high-density clusters. The gravitational influence of the gas was modeled using the tidal force of the cluster potential. For a given solar orbit, the mean density, 〈 ρ 〉 , was computed by orbit-averaging the density of material encountered. This parameter proved to be a good measure for predicting the properties of the OC. On average 2–18% of our initial sample of comets end up in the OC after 1–3 Myr. A comet is defined to be part of the OC if it is bound and has q > 35